EXPERIMENTAL AND CLINICAL STUDY OF PHENOTYPIC FEATURES OF S. EPIDERMIDIS STRAINS AND THEIR ROLE IN THE EMERGENCE AND DEVELOPMENT OF IMPLANT-ASSOCIATED INFECTION AFTER ORTHOPAEDIC SURGERY - S. A. Bozhkova; T. Y. Bogdanova; M. V. Krasnova; L. O. Anisimova; G. I. Netyl'ko; A. N. Rukina; B. Lyu (Travmatologiâ i Ortopediâ Rossii, 2016)
S. epidermidis is one of the most common cause of implant-associated infections. Infections due to S. epidermidis rarely develops into life-threatening, however, its prevalence and the difficulties in treating constitute a serious financial burden to the health care system. This study is based on the investigation of phenotypic features (ability to biofilm formation and resistance to antibiotics) of S. epidermidis strains isolated from patients with deep surgical site infection after implantation of orthopaedic devices, and on the investigation of the dynamics of clinical and morphological changes during the development of implant-associated infection due to S. epidermidis based on in vivo experimental models. Multidrug-resistance was found in 23% MSSE isolates and 97,3% - MRSE. Vancomycin, linezolid and fosfomycin were the most active in relation to these pathogens. About 40% of the tested isolates were strong biofilm-producing strains. 43,2% of MRSE strains and only 21,4% of MSSE isolates demonstrated strong biofilm production. The proposed experimental model shows that intra-operative infection of implant by multidrug-resistant clinical MRSE strain led to the development of osteomyelitis in rats for 4 weeks after surgery, in spite of the revision operation and installation of antimicrobial cement spacer in the area of bone defect. Thus, S. epidermidis is a clinically significant aetiological factor with high risk of development of infections after major orthopaedic surgery.